Exploring Students’ Presences in Online English Classroom: A Discourse Analysis - Genta Genta; Nida Husna; Didin Nuruddin Hidayat; Alek Alek (Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine how student presences (teaching, social, and cognitive) manifest in online discussions. This study takes place in a pragmatic class in English Magister Class where the researcher is also one of the students. The case study design was applied to this qualitative study, where the sample was taken purposively, consisting of 18 students and two lecturers. The data findings were analyzed using the Computer-Mediated Communication (CMC) act taxonomy by Herring et al. (2005). The results revealed that from three presences in Community of Inquiry (CoI), not all students were involved in the discussion, and not all problems or questions raised reached the resolution stage as the goal of cognitive presence. However, there is one thing that can be underlined in the master's study that the authors encountered is that there is no activity in the form of rejecting, which is a speech act that says that they do not agree with other people's opinions, so they look like they agree and follow the direction of the discussion as has been presented by the facilitator.